Activated Microglia Targeting Dendrimer–Minocycline Conjugate as Therapeutics for Neuroinflammation - Sharma, Rishi (Bioconjug Chem, 2017)
Brain-related disorders have outmatched cancer and cardiovascular diseases worldwide as the leading cause of morbidity and mortality. The lack of effective therapies and the relatively dry central nervous system (CNS) drug pipeline pose formidable challenge. Superior, targeted delivery of current clinically approved drugs may offer significant potential. Minocycline has shown promise for the treatment of neurological diseases owing to its ability to penetrate the blood–brain barrier (BBB) and potency. Despite its potential in the clinic and in preclinical models, the high doses needed to affect a positive therapeutic response have led to side effects. Targeted delivery of minocycline to the injured site and injured cells in the brain can be highly beneficial. Systemically administered hydroxyl poly(amidoamine) (PAMAM) generation-6 (G6) dendrimers have a longer blood circulation time and have been shown to cross the impaired BBB. We have successfully prepared and characterized the in vitro efficacy and in vivo targeting ability of hydroxyl-G6 PAMAM dendrimer–9-amino-minocycline conjugate (D-mino). Minocycline is a challenging drug to carry out chemical transformations due to its inherent instability. We used a combination of a highly efficient and mild copper catalyzed azide–alkyne click reaction (CuAAC) along with microwave energy to conjugate 9-amino-minocycline (mino) to the dendrimer surface via enzyme responsive linkages. D-mino was further evaluated for anti-inflammatory and antioxidant activity in lipopolysaccharides-activated murine microglial cells. D-mino conjugates enhanced the intracellular availability of the drug due to their rapid uptake, suppressed inflammatory cytokine tumor necrosis factor α (TNF-α) production, and reduced oxidative stress by suppressing nitric oxide production, all significantly better than the free drug. Fluorescently labeled dendrimer conjugate (Cy5–D-mino) was systematically administered (intravenous, 55 mg/kg) on postnatal day 1 to rabbit kits with a clinically relevant phenotype of cerebral palsy. The in vivo imaging study indicates that Cy5–D-mino crossed the impaired blood–brain barrier and co-localized with activated microglia at the periventricular white matter areas, including the corpus callosum and the angle of the lateral ventricle, with significant implications for positive therapeutic outcomes. The enhanced efficacy of D-mino, when combined with the inherent neuroinflammation-targeting capability of the PAMAM dendrimers, may provide new opportunities for targeted drug delivery to treat neurological disorders.